Hubungan Pengetahuan Ibu dan Sanitasi Fisik Rumah Terhadap Kejadian ISPA pada Balita di Wilayah Kerja Puskesmas Tarus - Sercy Servya; Soni Doke; Soleman Landi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
ARI is a chronic inflammatory disease that affects the airways from the nose to the alveoli, including tissues such as the sinuses/cavities around the nose. In Kupang Regency, ISPA cases experienced an increase in 2020 by 43,109 people, at the Tarus Health Center in 2020 there were 5,487 people. The aim of the study was to determine the relationship between the mother's level of knowledge and the physical sanitation of the house on the incidence of ARI in toddlers in the working area of ​​the Tarus Health Center. Types of analytical survey research. The research location was carried out in the working area of ​​the Tarus Public Health Center, Kupang Regency and was carried out from June to July 2022. The research population was mothers with toddlers, totaling 5,370 mothers of toddlers and a sample of 95 toddlers. The data analysis used was univariate and bivariate analysis with the Chi-Square statistical test with a 95% confidence level (α = 0.05). The results showed that the incidence of ARI was related to the mother's level of knowledge (p-value = 0.001), house ventilation (p-value = 0.004), occupancy density (p-value = 0.000), floor conditions (p-value = 0.003) , the condition of the walls of the house (p-value = 0.002), the age of the toddler (p-value = 0.000), the gender of the toddler (p-value = 0.000), but there is no relationship with cooking fuel (p-value = 0.596) with the incident ARI in the working area of ​​the Tarus Public Health Center, Kupang Regency. Puskesmas are expected to be able to utilize health promotion media in order to increase mothers' knowledge about the dangers of ARI and its prevention.